2017
DOI: 10.1177/2050312117701053
|View full text |Cite
|
Sign up to set email alerts
|

Novel combined patient instruction and discharge summary tool improves timeliness of documentation and outpatient provider satisfaction

Abstract: Background:Incomplete or delayed access to discharge information by outpatient providers and patients contributes to discontinuity of care and poor outcomes.Objective:To evaluate the effect of a new electronic discharge summary tool on the timeliness of documentation and communication with outpatient providers.Methods:In June 2012, we implemented an electronic discharge summary tool at our 145-bed university-affiliated Veterans Affairs hospital. The tool facilitates completion of a comprehensive discharge summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The needs for health lectures and online platforms were also unmet because of the existence of false information and digital gaps [ 34 , 35 ]. The accuracy of information was emphasized as a key to ensuring transitional care [ 36 ]. Therefore, it is urgent for transitional care teams to establish a reliable network platform and carry out credible TV education and health lectures.…”
Section: Discussionmentioning
confidence: 99%
“…The needs for health lectures and online platforms were also unmet because of the existence of false information and digital gaps [ 34 , 35 ]. The accuracy of information was emphasized as a key to ensuring transitional care [ 36 ]. Therefore, it is urgent for transitional care teams to establish a reliable network platform and carry out credible TV education and health lectures.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have sought to combat the delays in discharge summary distribution with innovative strategies such as electronic discharge summary programs. 4 , 7 , 8 Through a retrospective study, Reinke et al found that the electronic discharge summary programs increased the timeliness with which the discharge summaries were completed. Similarly, Gilliam et al used an electronic discharge summary tool to ensure that all discharge summaries were completed by the time of first postdischarge clinical contact, as opposed to 43% before their QI intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have sought to combat the delays in discharge summary distribution with innovative strategies such as electronic discharge summary programs 4,7,8 . Through a retrospective study, Reinke et al found that the electronic discharge summary programs increased the timeliness with which the discharge summaries were completed.…”
Section: Discussionmentioning
confidence: 99%
“…Today, some electronic health records systems are easily able to summarize medical data and save the time of care providers 11 . Various studies have indicated that utilizing an electronic summary sheet (ESS), even if it requires manual data entry by health care providers and does not pull the data automatically from the hospital database, is desirable among care providers and improves the completeness and quality of documentation 12,13 . Experts believe summary sheets that are created automatically, compared to those that are created manually or dictated, are more likely to be filled out more quickly and are more acceptable for health care providers in both outpatient and inpatient departments as a result 14 …”
Section: Introductionmentioning
confidence: 99%